Online Collaborative Learning Elements to Propose An Online Project Based Collaborative Learning Model - Razali, Sharifah Nadiyah; Shahbodin, Faaizah; Hussin, Hanipah; Bakar, Norasiken (2014)
Interest in collaboration is a natural outgrowth of the trend in education toward active learning. Many researchers have found that the advantages of collaborative learning; improves academic performance, promotes soft skills development (i.e., communications, collaboration, problem-solving and critical thinking skills), and increases satisfaction in the learning experience. Nevertheless, several studies have reported the complete opposite. In that respect, based on previous findings, three elements that are involved in the effectiveness of Online Collaborative Learning Environments are; Learning Environment, Learning Task, and Learning Interaction. This report proposes to determine the elements that can clarify all of the previously identified factors. Using the same approach as prior work, this study was conducted qualitatively; in the form of a document review. The outcome of this work suggests that (i) the learning interaction factor consists of learner-learner interaction and learner-teacher interaction elements, (ii) the elements of the learning design factor are content, process, evaluation, and time constraint, and (iii) usability, accessibility and stability are the ingredients of the learning environment factor. This study also proposes an Online Project-Based Collaborative Learning model. This model is currently only in a conceptual phase and requires significant development before it can be used to gather data. Therefore, in the next stage of this study, a prototype will be designed and developed; based on the proposed model.